2019
DOI: 10.1101/861898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swimming performance traits of twenty-one Australian fish species: a fish passage management tool for use in modified freshwater systems

Abstract: Freshwater ecosystems have been severely fragmented by artificial in-stream structures designed to manage water for human use. Significant efforts have been made to reconnect freshwater systems for fish movement, through the design and installation of dedicated fish passage structures (fishways) and by incorporating fish-sensitive design features into conventional infrastructure (e.g. culverts). Key to the success of these structures is making sure that the water velocities within them do not exceed the swimmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…Silver Perch activity patterns in the wild are generally greatest during daylight hours, however, they do not appear to be actively inhibited by darkness and can be trapped, albeit at lower frequencies, at night (Baumgartner et al 2008). In the present study, we were unable to disentangle a behavioural response to light levels from their response to water flow direction (rheotaxis), which may have been exacerbated by the relatively slow flow velocities used in this study compared to their swimming capacity (Watson et al 2019). For the two species that avoided the darkened environment, we found that the threshold light intensities needed to encourage individual fish to enter the darker half of the test channel were quite low.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Silver Perch activity patterns in the wild are generally greatest during daylight hours, however, they do not appear to be actively inhibited by darkness and can be trapped, albeit at lower frequencies, at night (Baumgartner et al 2008). In the present study, we were unable to disentangle a behavioural response to light levels from their response to water flow direction (rheotaxis), which may have been exacerbated by the relatively slow flow velocities used in this study compared to their swimming capacity (Watson et al 2019). For the two species that avoided the darkened environment, we found that the threshold light intensities needed to encourage individual fish to enter the darker half of the test channel were quite low.…”
Section: Discussioncontrasting
confidence: 56%
“…The channel bulk velocity was set to 0.3 m s-1 and the depth set to 0.15 m, measured at the mid-point, 6 m along the channel length. This velocity was chosen as it was significantly below the maximum sustainable swimming speed (Ucrit; Brett 1964) of all four species tested (Watson et al 2019) so as to minimise any effect that swimming capacity, or their innate rheotactic response, could have on their subsequent behaviour. The water temperature was maintained at 25 ± 1°C.…”
Section: Lightdark Behavioural Trialsmentioning
confidence: 99%
“…Silver Perch activity patterns in the wild are generally greatest during daylight hours, however, they do not appear to be actively inhibited by darkness and can be trapped, albeit at lower frequencies, at night (Baumgartner et al 2008). In the present study, we were unable to disentangle a behavioural response to light levels from their response to water flow direction (rheotaxis), which may have been exacerbated by the relatively slow flow velocities used in this study compared to their swimming capacity (Watson et al . 2019).…”
Section: Discussionmentioning
confidence: 75%
“…The channel bulk velocity was set to 0.3 m s-1 and the depth set to 0.15 m, measured at the mid-point, 6 m along the channel length. This velocity was chosen as it was significantly below the maximum sustainable swimming speed ( U crit; Brett 1964) of all four species tested (Watson et al 2019) so as to minimise any effect that swimming capacity, or their innate rheotactic response, could have on their subsequent behaviour. The water temperature was maintained at 25 ± 1°C.…”
Section: Methodsmentioning
confidence: 99%
“…Velocities in front of a typical trash rack can be as high as a few metres per second, exceeding the swimming capabilities of larval, juvenile and adult fish (Kopf et al . 2014; Watson et al in review). Therefore, smaller fish and debris may be sucked into the pump, while larger ones may be impinged on the trash rack.…”
Section: Introductionmentioning
confidence: 99%